INSTABILITY FOR A CERTAIN FUNCTIONAL DIFFERENTIAL EQUATION OF SIXTH ORDER - Cemil Tunc (Journal of the Indonesian Mathematical Society, 2011)
Sucient conditions are obtained for the instability of the zero solutionof a certain sixth order nonlinear functional dierential equation by the Lyapunov-Krasovskii functional approach. DOI : http://dx.doi.org/10.22342/jims.17.2.7.123-128